Empirical study of protective products in an emerging market. Issue 1 (21st September 2021) - Li, Xinrong; Guo, Tao; Guo, Dongmei
Abstract : Purpose: This paper aims to study the motivations for purchasing protective products. Design/methodology/approach: Empirical microeconomic research. Findings: The results show that comparing with ordinary families, families vulnerable to environmental conditions, including prepregnant, pregnant and postpartum families, are not intended to consume more protective products. Among the above three types of families, postpartum families consume the most, followed by pregnant families, and prepregnancy families consume the least. The results also showed that a higher level of economic development, more prevalent Internet access and higher levels of education also increase the consumption of protective products. Originality/value: New dataset and new empirical results.